Diagnostic value of presurgical 68Ga-PSMA-11 PET/CT in prostate cancer patients with different ISUP grade groups - Okudan, Berna; Atalay, Merve; Hakkoymaz, Zeynep Ruken; Seven, Bedri; Öcal, Berrak Gümüşkaya (Nuklearmedizin - NuclearMedicine, 2025)
In our study, we aimed to investigate the correlation of preoperative 68Ga-PSMA PET/CT imaging with pathology findings obtained from radical prostatectomy in patients diagnosed with adenocarcinoma by prostate biopsy.A total of 76 consecutive patients who were diagnosed prostate adenocarcinoma as a result of biopsy between 2019–2021 and who underwent 68Ga-PSMA PET/CT imaging were retrospectively analyzed. The localization of the pathologically evaluated activity involvement areas, the largest diameter and SUVmax values were recorded. Sections of prostatectomy materials belonging to all cases were removed from the archive and re-evaluated by an experienced pathologist, and tumor areas were marked. As the gold standard, slices sampled in accordance with classical prostatectomy macroscopy rules were arranged from proximal to distal, the lesions were mapped, dominant nodule diameter and localization, lymph node (LN) metastases and seminal vesicle invasion (SVI) were recorded.Among 61 patients who underwent pelvic LN dissection, PET/CT was able to detect 16 of 18 patients with LN metastases. In the statistical analysis, a high degree of agreement was found between the histopathological and PET/CT results (p<0.05). Furthermore, a high degree of agreement was also observed between histopathological and PET/CT findings for detection of SVI (Kappa=0.808, p<0.05 for the right side and Kappa=0.774, p<0.05 for the left side).The findings of this study indicate that 68Ga-PSMA PET/CT can be used to determine the localization and extent of prostate cancer. 68Ga-PSMA PET/CT before radical prostatectomy can help identify target lesions and aid in decision-making regarding therapy.
Keywords: pathology; prostate cancer; prostatectomy; PET/CT; PSMA